2003
DOI: 10.1002/cncr.11362
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid neoplasms after therapeutic radiation for malignancies during childhood or adolescence

Abstract: BACKGROUNDRecent data indicate that the risk of developing a thyroid neoplasm clearly is increased after high‐dose, therapeutic radiation therapy during childhood. To better understand the time course, natural history, and histopathology of thyroid lesions that develop after high‐dose irradiation, the authors undertook a retrospective study of all survivors of childhood and adolescent malignancies who were treated at Memorial Sloan‐Kettering Cancer Center and who developed a clinically apparent thyroid neoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
1
11

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(92 citation statements)
references
References 37 publications
6
74
1
11
Order By: Relevance
“…This subtype is the most frequent one, not only in the general population, but also following treatment for childhood malignancy. 11,13,37,38,40,41 Some authors found that being less than 10 years of age was associated with an increased risk of thyroid cancer, 11,13,38 although we did not find similar results. In contrast, we confirmed that women are at an increased risk of developing thyroid cancer (HR=4.74; P=0.002), which has been suggested by other studies 13 and observed in the general population.…”
Section: Discussioncontrasting
confidence: 95%
“…This subtype is the most frequent one, not only in the general population, but also following treatment for childhood malignancy. 11,13,37,38,40,41 Some authors found that being less than 10 years of age was associated with an increased risk of thyroid cancer, 11,13,38 although we did not find similar results. In contrast, we confirmed that women are at an increased risk of developing thyroid cancer (HR=4.74; P=0.002), which has been suggested by other studies 13 and observed in the general population.…”
Section: Discussioncontrasting
confidence: 95%
“…A distinctive finding was the high frequency of multicentricity, but the baseline and treatment factors related to recurrence were very similar to those for thyroid cancer patients in the general population. Based on this and the findings of others we recommended that patients with radiationrelated thyroid cancer should be treated in the same way as unexposed patients with thyroid cancer (2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 70%
“…The nodules were bilateral in eight (38%) of the 21 patients. Nodule diameter ranged from 6 to 40 mm, with a median value of 13.7 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) mm.…”
Section: Ultrasound Findingsmentioning
confidence: 99%
“…Studies on patients receiving irradiation treatment for various cancers have reported a high frequency of benign and malignant thyroid nodules. The reported relative risks for thyroid nodules among the survivors of pediatric cancers who have undergone radiation therapy vary greatly, with an incidence of malignancy of 10-40% (6,7,8,9,10,11,12,13). Analysis of studies evaluating thyroid carcinoma after exposure to external radiation during childhood showed that the dose-response relationship was linear, although the risk appeared to plateau at the highest dose, with risk appearing to slightly decrease at doses of even more than 2000 cGy (9,11,13,14,15,16).…”
Section: Introductionmentioning
confidence: 99%